Um novo IVA? : adaptações do Imposto sobre Valor Agregado para a economia digital - Castello, Melissa Guimarães (2021)
The thesis focuses on the analysis of the suitability of Value Added Tax, with its present characteristics, to the digital economy. To this end, the structuring principles and the functioning of VAT are accessed (with emphasis on the European VAT and the Brazilian ICMS). This study uses the theory developed by Paulo de Barros Carvalho to identify the main elements of a VAT. Then, we move on to define what is meant by consumption arrangements of the digital economy, examining these new business models in the light of Schumpeter's theory. Finally, the adaptations of VAT to the digital economy are examined. One concludes that, due to changes in the consumption arrangements of the 21st Century, VAT should undergo changes in its structure. In particular, a VAT must be formulated with a broad tax base - “carrying out any operation with value added” - and it should follow the destination principle. There must also be adjustments in the cross border liability, establishing new responsibilities for collecting the tax. Thus, the adequate collection in international or regional operations will be secured.